Technological Embeddedness of Inter-organizational Collaboration Processes - Cepa, Katharina; Schildt, Henri (Managing Inter-Organizational Collaborations, 2019)
Abstract Advanced information technologies, and particularly big data, provide new affordances to facilitate inter-organizational collaboration. Rich flows of real-time data provide transparency across organizational boundaries and enable greater automation of inter-organizational routines. Taking stock of the literature and building on observations from the research in an industrial setting, the authors introduce the concept of technological embeddedness as an important characteristic of inter-organizational relationships, denoting the degree of monitoring, control, and optimization of intra- and inter-organizational tasks accomplished through technology at the interface of the inter-organizational relationship. The authors theorize how increasing technological embeddedness created by big data technologies affects the development of inter-organizational trust, mutual adaptation, and temporal structuring of collaboration. The propositions elaborate how greater technological embeddedness enables collaboration, and warn about the potential limiting effects of technological embeddedness on the development of interpersonal trust, strategic learning, and long-term orientation.